SURGICAL OUTCOME OF TRANSPEDICULAR FIXATION IN THORACOLUMBER FRACTURES - Khan, Abdul Aziz; Khanzada, Khalid; Ayub, Shahid; Ali, Mumtaz (Journal of Ayub Medical College Abbottabad, 2008)
Background: Development of transpedicular screw fixation techniques and instrumentation systems has brought short-segment instrumentation (fixation of one normal vertebra above and below an injured segment) into general clinical practice. The purpose of this study is to report the surgical outcome of thoracolumber fractures treated with short-segment pedicle instrumentation. Methods: A retrospective review of all surgically managed thoracolumbar fractures during two years was performed. The 84 surgically managed patients were instrumented by the short-segment technique. Patients charts, operation notes, preoperative and postoperative radiographs, computed tomographic scans, magnetic resonance imaging (MRI) was done. Neurological findings (Frankel functional classification), and follow-up records up to 6 months were reviewed. Results: Transpedicular fixation was performed in 84 cases including 52 male and 32 female with male to female ratio 1.6:1. Mean±SD of age was 40±13.75 years (range15-60). The level of injuries was different in different age groups. Outcome was assessed on Frankle grading. No patient showed an increase in neurological deficit. Most of the patients showed improvement to the next grade. Screw breakage occurred in 8 cases, bed sores in 16 cases and deep vein thrombosis in 3 cases. Misplaced screw in 5 cases. Eight cases got wound infection. Conclusion: Although long term follow-up evaluation needs to verified, the short term follow-up results suggest a favourable outcome for short-segment instrumentation. Keywords: Pedicle screw instrumentation, Thoracolumbar fracture, Short-segment, Fixation.